2011
DOI: 10.1007/s10707-011-0122-y
|View full text |Cite
|
Sign up to set email alerts
|

MOVIES: indexing moving objects by shooting index images

Abstract: With the exponential growth of moving objects data to the Gigabyte range, it has become critical to develop effective techniques for indexing, updating, and querying these massive data sets. To meet the high update rate as well as low query response time requirements of moving object applications, this paper takes a novel approach in moving object indexing. In our approach, we do not require a sophisticated index structure that needs to be adjusted for each incoming update. Rather, we construct conceptually si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Thus we need not support updates and can use efficient bulk-loading methods. We evaluate four different choices of static index: the R-Tree [14,22], the CR-Tree [21], the Linearized KDTrie [9,29] and a Simple Static Grid [38]. R-Tree.…”
Section: Static Index Nested Loops Join Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus we need not support updates and can use efficient bulk-loading methods. We evaluate four different choices of static index: the R-Tree [14,22], the CR-Tree [21], the Linearized KDTrie [9,29] and a Simple Static Grid [38]. R-Tree.…”
Section: Static Index Nested Loops Join Methodsmentioning
confidence: 99%
“…On one hand, we can use methods specifically designed for moving objects, such as the TPRTree [37]. On the other hand, if queries and updates can be processed in bulk, then it may be faster to re-execute a static join or rebuild a static index to deal with every batch of queries and updates [9,40]. It is clear that rebuild approaches should outperform incremental updates when batch sizes approach the total number of objects.…”
Section: Background 21 Moving Object Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have observed that all of the example applications above, as well as many others, can be run completely in main memory. Furthermore, several recent studies have argued that many moving-object applications, including traditional location based services such as flight tracking, can tolerate some query staleness [DBVS11,ŠRJŠ11]. However, these applications require very low response times even in the presence of significant query and update rates.…”
Section: Benchmarking Spatial Indexingmentioning
confidence: 99%